Transduction of Neural Precursor Cells with TAT‐Heat Shock Protein 70 Chaperone: Therapeutic Potential Against Ischemic Stroke after Intrastriatal and Systemic Transplantation12. (15th May 2012) - Doeppner, Thorsten R.; Ewert, Tobias A. S.; Tönges, Lars; Herz, Josephine; Zechariah, Anil; ElAli, Ayman; Ludwig, Anna‐Kristin; Giebel, Bernd; Nagel, Florian; Dietz, Gunnar P. H.; Weise, Jens; Hermann, Dirk M.; et al.
Abstract: Novel therapeutic concepts against cerebral ischemia focus on cell‐based therapies in order to overcome some of the side effects of thrombolytic therapy. However, cell‐based therapies are hampered because of restricted understanding regarding optimal cell transplantation routes and due to low survival rates of grafted cells. We therefore transplanted adult green fluorescence protein positive neural precursor cells (NPCs) either intravenously (systemic) or intrastriatally (intracerebrally) 6 hours after stroke in mice. To enhance survival of NPCs, cells were in vitro protein‐transduced with TAT‐heat shock protein 70 (Hsp70) before transplantation followed by a systematic analysis of brain injury and underlying mechanisms depending on cell delivery routes. Transduction of NPCs with TAT‐Hsp70 resulted in increased intracerebral numbers of grafted NPCs after intracerebral but not after systemic transplantation. Whereas systemic delivery of either native or transduced NPCs yielded sustained neuroprotection and induced neurological recovery, only TAT‐Hsp70‐transduced NPCs prevented secondary neuronal degeneration after intracerebral delivery that was associated with enhanced functional outcome. Furthermore, intracerebral transplantation of TAT‐Hsp70‐transduced NPCs enhanced postischemic neurogenesis and induced sustained high levels of brain‐derived neurotrophic factor, glial cell line‐derived neurotrophic factor, and vascular endothelial growth factor in vivo. Neuroprotection after intracerebral cell delivery correlated with the amount of surviving NPCs. On the contrary, systemic delivery of NPCs mediated acute neuroprotection via stabilization of the blood‐brain‐barrier, concomitant with reduced activation of matrix metalloprotease 9 and decreased formation of reactive oxygen species. Our findings imply two different mechanisms of action of intracerebrally and systemically transplanted NPCs, indicating that systemic NPC delivery might be more feasible for translational stroke concepts, lacking a need of in vitro manipulation of NPCs to induce long‐term neuroprotection. STEM CELLS 2012;30:1297–1310